Detection of herpesviruses and enteroviruses in patients with suspected infectious meningoencephalitis in three referral hospitals in Yaounde, Cameroon. Issue 12 (24th June 2020) - Tagnouokam‐Ngoupo, Paul Alain; Toby, Roselyne; Bomba Ebede, Michelle Olivia; Kenmoe, Sebastien; Ngo‐Malabo, Elodie Teclaire; Sadeuh‐Mba, Serge Alain; Biwole‐Sida, Magloire; Njouom, Richard
Abstract: In Cameroon, routine diagnosis of central nervous system (CNS) infections is based on the detection of bacteria, fungi, parasites, and mycobacteria in cerebrospinal fluids. Therefore, there is no data on viral etiologies of meningoencephalitis (ME) in the country. We aim to identify viral etiologies (herpesviruses and enteroviruses) of ME in Cameroon, to provide useful information to physicians that will help improving management of ME. From February to May 2018, adult patients with clinical signs of ME in three referral hospitals in Yaounde were included. Detection of herpesviruses and enteroviruses was performed using reverse transcriptase polymerase chain reaction. P value of 5% was chosen as the threshold for statistical significance in statistical analyses. Eighty‐one patients were included and 15 (18.51%) were positive for herpesviruses. No enterovirus was detected. The most prevalent virus was Epstein‐Barr virus (8.6%) and most of herpesviruses were detected from human immunodefeciency virus (HIV)‐positive patients (86.7%). The overall mortality rate was high, 60.5% (49/81) and analysis of risk factors showed that HIV‐positive status and altered state of consciousness were associated with higher risk of death (odds ratio [OR], 5.41; confidence interval [CI]: 1.91‐16.88; P = .002 and OR, 3.24; CI: 1.11‐0.13; P = .036 respectively). We showed that herpesviruses are present in patients with ME symptoms in Yaounde and can be sometimes in coinfection with others common pathogens of CNS infections. There is therefore a need for increased clinician awareness and education regarding the diagnostic and management of CNS infections in Cameroon to limit unnecessary use of antibiotics. Highlights: No data on the viral etiologies of meningoencephalitis (ME) in Cameroon. Herpesviruses and enteroviruses were screened in patients with clinical signs of ME. 18.51% patients were positive for herpesviruses and no enterovirus was detected The most prevalent virus was Epstein‐Barr virus (8.6%) and most of herpesviruses were detected from HIV‐positive patients (86.7%)